(untitled) (In situ, 2024)
In March 2023, the second phase of archaeological excavations was carried out at Lergova Gradina, a Liburnian settlement with an imposing rampart. Trial trench 3 was opened, which in the upper part contained various finds from the last centuries BC, such as amphora fragments and north African coins. Pottery dating to the Middle Bronze Age was found at the bottom of the trial trench.